The Chinese Perspective towards Spain from the Tardofranquismo to the Present Day Rafael (Comillas Journal of International Relations, 2019)
This article talks about the issue of the image projected by Spain in the Chinese government and its citizenship from the last years of Franco, coinciding with the moment of the agreement between the two countries, until the present day. Spain was, until almost the end of the eighties, a country whose political changes caused a direct reaction in the Chinese governmental perspective that greatly influenced the type of treatment given in the newspapers about the country. At the same time, a personalist diplomacy is being developed from Spain to China from the late seventies to the mid-eighties that will create a permanent but diffuse image in the Chinese imaginary about Spain. From that moment, and by the reason of the good harmony between the Spanish and Chinese governments, but the scarce Hispanic presence in the live of the country, will appear two different perspectives, the government and the citizen, until the actual situation, in which Spain , without a specific plan of image, has been dragged into the world of imaginary topics in the perspective of Chinese citizens, which will lead to its corresponding diplomatic reflexion of the Chinese government to Spanish in the years ahead.
Keywords: perspective; image; government; citizenship; mass media